Single opsin driven white noise ERGs in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (Frontiers in Neuroscience, 2023)
Purpose: Electroretinograms to photopigment isolating white noise stimuli (wnERGs) in mice were measured. The dependency of rod-and cone-opsin-driven wnERGs on mean luminance was studied.Methods: Temporal white noise stimuli (containing all frequencies up to 20 Hz, equal amplitudes, random phases) that modulated either rhodopsin, S-opsin or L*-opsin, using the double silent substitution technique, were used to record wnERGs in mice expressing a human L*-opsin instead of the native murine M-opsin. Responses were recorded at 4 mean luminances (MLs). calculated from MTF phases showing high delays for rhodopsin-vs. low delays for L*-opsin-driven responses.Conclusions: Opsin-isolating wnERGs in mice show characteristics of different retinal cell types and their connected pathways.